Winning Armageddon Curtis LeMay and Strategic Air Command, 1948-1957. - Albertson, Trever (History of military aviation., 2019)
This book provides definition to an all-too-long neglected figure of the Cold War, General Curtis E. LeMay, and tells the story of his advocacy for nuclear first strikes while leading Strategic Air Command-the Cold War Air Force's nuclear organization.